Perancangan Sistem Informasi Penggajian Berbasis Web Dengan Metode Rapid Application Development - Reni Haerani; Hera Resti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Payroll is a system that regulates the payment of wages or salaries to all employees for the services they provide in an organization or business. However, not all companies have a good payroll system. Some of them are still done manually, in this case salary calculations still use manual calculation methods that have not been computerized. This was considered ineffective and inefficient due to the length of time it took to process information management and frequent errors in payroll.One solution to simplify employee payroll is a web-based payroll application. The purpose of this research is to simplify and create a Web-based employee salary information system at PT. Adidaya Sentosa Abadi is more efficient and organized than before. The research methods are observation, interviews, and literature study. The software development model used is Rapid Application Development. This model enables an optimized development process to achieve a system with low investment costs. The results showed that computer data processing is generally easier and the results of data processing are more accurate than manual processing. The proposed payroll system uses PHP Programming and web-based MySQL database to simplify the payroll process, making is faster, more accurate, and easier to maintain. Keywords—Information System, Payroll, Rapid Application Development